An Integrative Taxonomy Approach Reveals Saccharomyces Chiloensis Sp. Nov. as a Newly Discovered Species from Coastal Patagonia - Cubillos-Riffo, F; Villarreal-Diaz, P; Pena-Echeverria, T; Urbina, K (Public Library of Science, 2024)
Species delineation in microorganisms is challenging due to the limited markers available for accurate species assignment. Here, we applied an integrative taxonomy approach, combining extensive sampling, whole-genome sequence-based classification, phenotypic profiling, and assessment of interspecific reproductive isolation. Our work reveals the presence of a distinct Saccharomyces lineage in Nothofagus forests of coastal Patagonia. This lineage, designated Saccharomyces chiloensis sp. nov., exhibits 7% genetic divergence from its sister species S. uvarum, as revealed by whole-genome sequencing and population analyses. The South America-C (SA-C) coastal Patagonia population forms a unique clade closely related to a previously described divergent S. uvarum population from Oceania (AUS, found in Australia and New Zealand). Our species reclassification is supported by a low Ortho Average Nucleotide Identity (OANI) of 93% in SA-C and AUS relative to S. uvarum, which falls below the suggested species delineation threshold of 95%, indicating an independent evolutionary lineage. Hybrid spore viability assessment provided compelling evidence that SA-C and AUS are reproductively isolated from S. uvarum. In addition, we found unique structural variants between S. chiloensis sp. nov. lineages, including large-scale chromosomal translocations and inversions, together with a distinct phenotypic profile, emphasizing their intraspecies genetic distinctiveness. We suggest that S. chiloensis sp. nov diverged from S. uvarum in allopatry due to glaciation, followed by post-glacial dispersal, resulting in distinct lineages on opposite sides of the Pacific Ocean. The discovery of S. chiloensis sp. nov. illustrates the uniqueness of Patagonia’s coastal biodiversity and underscores the importance of adopting an integrative taxonomic approach in species delineation to unveil cryptic microbial species. The holotype of S. chiloensis sp. nov. is CBS 18620T © 2024 Peña et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.